Women letter-writers in Tudor England - Daybell, James, 1972-; Oxford eBooks (Oxford : Oxford University Press, 2006)
Presenting a comprehensive study of women's letters and letter-writing in early modern England, this text draws on over 3,000 manuscript letters, showing that letter-writing was a large and socially diversified area of female activity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English letters -- Women authors -- History and criticism; English literature -- Early modern, 1500-1700 -- History and criticism; Women and literature -- Great Britain -- History -- 16th century; Electronic books